Pliniusz Starszy o zasobach naturalnych Hiszpanii i ich wykorzystaniu - Danek, Zbigniew (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
Many references to Spain found in Naturalis Historia written by Pliny the Elder prove his profound knowledge of the land and culture of Spain, as well as his particular recognition of the wealth and high economic level of this country. Pliny the Elder gives important information about the agricultural resources of Spain and the basic crops of this land, which include mainly corn, vine and spartum, or Lygeum spartum, which is a valuable textile material, but he mainly focuses on the unusual wealth of minerals that were obtained from local excavations. Among them were materials useful for the production of medicines, dyes or ceramics, but also materials necessary for the production and preservation of food (enough to mention salt, extracted in Spain on a large scale), but mainly he describes precious metals, i.e., silver and gold, which made the Iberian Peninsula famous at that time. The manner in which Pliny depicts the mining techniques used at that time indicates his astonishing knowledge of the described realities, and the remarks which he provides about the destructive methods of obtaining Spanish gold testify to his ecological commitment to the integrity and undisturbed prosperity of the country with which he was connected in 73 AD by the prosecutor’s office.